The effect of heat treatment on hardness properties and microstructure of 9Cr-Mo-V T91 alloy steel - Jaafar, Che Nor Aiza; Saleh, Mat Husin; Noraslan, Nurul Zawanah; Zainol, Ismail; Md Rezali, Khairil Anas; Anene, Franklin; Dele-Afolabi, Temitope Theophilus (Universiti Putra Malaysia, 2022)
The effect of heat treatment on hardness properties and microstructure of 9Cr-Mo-V T91 alloy steel have been investigated. In this study, T91 alloy steel were austenitized at 1050 °C for 40 minutes and then quenched in different media such as forced air, air at room temperature, sand and furnace. The austenitization was followed by tempering at 730 °C for 40 minutes with two different quenching media (water and air). The hardness of all T91 steels with different conditions was measured using Micro-Vickers hardness test. The microstructure analyses were examined using optical microscope and field emission scanning electron microscopy (FESEM), while electron dispersive x-ray (EDX) with low kV mode, was used to analyse the chemical compositions of the precipitate in T91 tempered alloy steel. It can be seen from hardness results, the austenitized T91 steel cooled in furnace had shown large grain size and boundaries of ferrite in a martensitic structure which caused decreased in hardness properties. Tempered alloy steel showed the decreased in the hardness value as compared to the austenitized condition due to the coarsening of carbides and breakdown of lath martensitic. Based on EDX analysis, it was confirmed that iron (Fe) and chromium (Cr) were indeed the highest alloying element in T91 alloy steel, and carbide precipitations of M23C6 are dispersed along the prior austenite grain boundaries (PAGB) and sub-grains. Slowest quenching rate after austenitization, which is furnace cooling, was proven to produce ferrite in the matrix of martensite which caused premature failure of T91 alloy steels used in power plant industries. FESEM/EDX utilizing low kV mode (15 kV) was able to analyse precipitate successfully.